Comparison of white matter hyperintensity abnormalities and cognitive performance in individuals with low and high cardiovascular risk: Data from the Diabetes and Dementia (D2) study. (31st December 2021) - Restrepo, Carolina; Patel, Sheila; Khlif, Mohamed Salah; Bird, Laura J.; Singleton, Rebecca; Yiu, Chi Him Kendrick; Werden, Emilio; Ekinci, Elif; MacIsaac, Richard; Burrell, Louise; Brodtmann, Amy
Abstract: Background: Type 2 diabetes Mellitus (T2DM) is recognised as a major contributor to cognitive decline. People with T2DM demonstrate increased white matter hyperintensity (WMH) abnormalities on MRI compared to control individuals. We investigated associations between a validated vascular risk score: The Framingham Risk Score (FRS), WMH volumes and cognitive function in the Diabetes‐and‐Dementia (D2) study, a longitudinal cohort study of community dwelling people with T2DM. Method: One hundred and twenty‐three non‐demented participants with T2DM (age 66.7±6.8 years, range 50‐80, 68M/55F) completed neuropsychological assessments, health questionnaires to allow FRS calculation, 24‐hour ambulatory blood pressure monitoring, and a 3T‐MRI scan. WMH were calculated using the functionality "run‐samseg" in FreeSurfer 7. Quality control on the traced lesions was performed using an in‐house semi‐automated MATLAB tool. Periventricular and deep WMH volumes were estimated based on the edited lesion traces. We divided participants into low (n=61) and high (n=62) FRS groups based on the median score (x=48.7). Differences in WMH volumes were compared between the FRS groups after correcting for sex and age. We compared cognitive performance between low/high FRS individuals across five composite cognitive domains: memory, language, visuospatial skills, executive function, and attention‐and‐processing‐speed. The composite score for each domain was the normalised z‐scores average for the respective tests. Result: Participants with high FRS (implicating greater vascular risk) were significantly older (age F(1, 122)=14.97; p <0.001), were less likely to be female (sex χ 2 =16.73, p <0.001), and tend to have less than 12 years of education (χ 2 = 3.69, p = 0.041). Relative to individuals with low FRS, those with high FRS showed significantly higher WMH volumes (F(1, 121)=6.11; p =0.015). Significant differences were also identified for periventricular (F(1, 121)=6.16; p =0.014) and deep (F(1, 121)=4.25; p =0.042) WMH volumes. When the cognitive data were analysed, the low FRS group performed signifcantly better than the high FRS group only on the attention‐and‐processing‐speed factor (F(1, 115)=5.17; p =0.025). Conclusion: High cardiovascular risk, defined as a high FRS, in participants with T2DM was associated with greater WMH volume, a marker of white matter dysfunction, and with deficits in processing speed and attention. Subclinical cognitive deficits were common in our community dwelling cohort without known or preceding cognitive dysfunction.